The Sharing Approach to Teaching Cross-Cultural Understanding: Evidence from University Students’ Perspective - Basori, Basori; Maharany, Elva Riezky; Rofiki, Imam (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
In the current global era, there is a distinct need for cross-cultural understanding (CCU) instruction. This study endeavored to explore participants' perspectives following the completion of a course designed to enhance students' CCU knowledge and appreciation for diversity through a sharing approach. Data were collected via questionnaires and reflection reports, which were distributed to university students through Google Forms. Utilizing an explanatory sequential design, the study involved 18 university students enrolled in the Nusantara Module. The findings indicated a positive acceptance of the sharing approach among the students. Furthermore, the students revealed that their sense of nationalism remained intact despite exposure to different cultures. These results have several implications, including a promising direction for the development of more effective CCU courses and the potential of educational programs to augment global understanding without undermining national identity. Nevertheless, further research is needed to validate these findings across diverse settings and demographics. Future studies may also explore the long-term effects of the sharing approach on students' attitudes towards cultural diversity.